Enhancing Geometry Learning Outcomes: The Role of Augmented Reality Media in Mathematics Education - Maria Angela Christin Tefa; Fikri Aulia; Taufik Ikhsan Slamet (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2025)
The advancement of digital technology drives the integration of technology in mathematics education to overcome students' difficulties in understanding abstract concepts, particularly in geometry. One technology with significant potential to support such learning is Augmented Reality (AR), which enables the interactive visualization of three-dimensional objects. This study aims to systematically review the effectiveness of Augmented Reality media in improving mathematics learning outcomes and to identify the supporting factors and barriers to its implementation in geometry learning for Junior High School students. The research method employed is a Systematic Literature Review (SLR) following the PRISMA protocol. Literature searches were conducted across the Scopus, Google Scholar, and ERIC databases for publications between 2020 and 2025, resulting in 10 articles that met the inclusion criteria. The synthesis results indicate that the use of AR media consistently enhances mathematics learning outcomes, conceptual understanding, spatial abilities, as well as student engagement and motivation. The effectiveness of AR is supported by its interactive three-dimensional visualization, ease of use, positive student responses, and integration with student-centered learning models. However, the implementation of AR still faces barriers such as infrastructure limitations, teacher readiness, and the potential for student distraction if not pedagogically well-designed. Thus, Augmented Reality media holds substantial potential as an innovative learning tool in geometry education, particularly for three-dimensional shapes, provided it is supported by adequate instructional planning and implementation readiness